(Pseudo)spin symmetry in the single-neutron spectrum of Λ hypernuclei. (2nd November 2017) - Lu 吕万, W-L 里; Liu 刘子, Z-X 鑫; Ren 任素, S-H 红; Zhang 张, W 炜; Sun 孙亭, T-T 亭
Abstract: Pseudospin and spin symmetries in the single-neutron spectra of Λ hypernuclei, and the effects of Λ impurity on these symmetries, are studied in the relativistic mean field model. It is found that the spin symmetry is violated while the pseudospin symmetry is approximately conserved, which is similar to the case in ordinary nuclei. As an impurity, the Λ hyperon makes the spin symmetry worse while making the pseudospin symmetry better, which arises from the decrease in the centrifugal barrier and the increase in the pseudo-centrifugal barrier in their competitions with the spin–orbit and pseudospin–orbit potentials, respectively. Further, our investigation extended to the Sn isotopes with 0 Λ, 1 Λ, and 2 Λ, and indicated that the effects of Λ impurity on pseudospin and spin symmetries are universal.